2021
DOI: 10.3389/fvets.2021.688936
|View full text |Cite|
|
Sign up to set email alerts
|

Overview of Control Programs for Cattle Diseases in Finland

Abstract: Animal disease control has a long tradition in Finland. The country is free of all EU-regulated cattle diseases of categories A and B. Infectious bovine rhinotracheitis, enzootic bovine leucosis, bovine viral diarrhea, bluetongue, bovine genital campylobacteriosis, and trichomoniasis do not currently exist in the country. The prevalence of paratuberculosis, Mycoplasma bovis, salmonella infection, and Q-fever is low. The geographic location, cold climate, low cattle density, and limited animal imports have cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…In fact, one of the main challenges regarding the control of Salmonella is the prevalence levels among animal populations. In Europe, several countries have implemented strict Salmonella surveillance and control programs for poultry (broilers, turkeys, and laying hens) [44][45][46] and, to a lesser extent, for pigs [47] and cattle [48][49][50][51]. Generally, these programs rely on the collection of samples for Salmonella detection and on the implementation of restrictions on farms whenever positive results are found.…”
Section: Food Production Chains and Salmonellamentioning
confidence: 99%
“…In fact, one of the main challenges regarding the control of Salmonella is the prevalence levels among animal populations. In Europe, several countries have implemented strict Salmonella surveillance and control programs for poultry (broilers, turkeys, and laying hens) [44][45][46] and, to a lesser extent, for pigs [47] and cattle [48][49][50][51]. Generally, these programs rely on the collection of samples for Salmonella detection and on the implementation of restrictions on farms whenever positive results are found.…”
Section: Food Production Chains and Salmonellamentioning
confidence: 99%
“…However, other endemic countries endeavor to contain infections at the farm level through culling or isolating infected animals ( 133 ). Finland, for example, pursues a voluntary control program involving farmers since M. bovis is regarded as one of less serious diseases ( 134 ).…”
Section: Control and Prevention Measuresmentioning
confidence: 99%
“…Namonyo et al used rumen viral metagenomics to show that bacteriophages are the majority of the rumen viruses and play a key role in keeping the population count of bacteria in the microbiome of the rumen under the carrying capacity, which is vital for the health of sheep and goats [101]. Viral metagenomics is also useful for identifying causative agents from many animal diseases that could negatively affect food production [102,103]. For example, Wüthrich et al identified six potential viral causes of non-suppurative encephalitis in cattle: PIV-5, BoAstV-CH13/NeuroS1, bPyV-2 SF, OvHV-2, BHV-6, and BoRV-CH15, through viral metagenomics sequencing [104].…”
Section: Viral Metagenomicsmentioning
confidence: 99%